Peta Informasi Penyusutan Aset Tetap Menggunakan Metode Garis Lurus - Dedi Suhendro; Ade Septian Hasibuan; Candra Wiranto Sitorus (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
The depreciation system for fixed assets in this study uses the straight-line method and develops a computerized asset depreciation information system. The research subject is PT Perkebunan Nusantara III (persero) special area of ​​Sei Mangkei, Simalungun Regency and the object of research regarding the depreciation system of fixed assets using the straight-line method. Depreciation of these assets includes depreciation of buildings, office equipment, vehicles and other fixed assets used in research, with data collection techniques used including interviews, observations and library studies. The results show that the development of a fixed asset depreciation system using the straight-line method can process data when calculating depreciation costs, and depreciation reports required by PT Perkebunan Nusantara III (persero).